Pengaruh Korean Brand Ambassador dan Loyalitas Pelanggan terhadap Keputusan Pembelian pada Pengguna Shopee di Kota Medan: Penelitian - Nova Sinambela; Onan Marakali Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the influence of Korean brand ambassadors and customer loyalty on purchasing decisions among Shopee users in Medan City. The type of research used in this study is quantitative research with an associative approach. Sampling was conducted using purposive sampling techniques and involved 100 respondents as the sample. The results of the research conducted show that the variable korean brand ambassador (X1) and customer loyalty (X2) have a positive and significant effect on purchasing decisions (Y) both partially and simultaneously. The coefficient of determination test shows that there is a very strong relationship between the korean brand ambassador variable and customer loyalty towards the purchasing decision with an R value of 0.783. Through the adjusted R square value, it is also known that the korean brand ambassador and customer loyalty variables contribute 60.6% to the purchasing decision variable, while the remaining 39.4% is influenced by other variables not discussed in this study.